TERM KECERDASAN DI DALAM AL QUR’AN - Amsori Amsori (Universitas Islam Depok, 2021)
If we look at the analysis of the position of reason in Islam, then Islam really glorifies reason. While most people have the full spectrum of intelligence, individuals exhibit different cognitive traits.